Evaluating the Performance Characteristics of Pressure Monitoring Systems - Silvia Caggiari; Liudi Jiang; Peter Worsley (Sensors)
Measuring interface pressure is currently used in a variety of settings, e.g., automotive or clinical, to evaluate pressure distribution at support surface interfaces. Commercial pressure sensing arrays are employed to monitor and visualise these pressure distributions to aid mattress or cushion selection by assessing their ability to redistribute the pressure magnitudes over vulnerable areas, e.g., the buttock. These technologies vary in configurations and measurement principles, with manufacturers supplying calibration and specifications. This study evaluated the performance of six commercial pressure sensing arrays, which differed in sensor type, configuration, and spatial resolution. Each system was subjected to mechanical compression loading on a standard cushion using a dual hemispherical ‘buttock shaped’ standard indenter. Pressure parameters were estimated, e.g., contact area, peak pressure index, from the sensing arrays and a comparison between measured and predicted pressure values was performed. The results showed that both contact area and pressures are influenced by the spatial resolution, with higher values associated with systems with the highest resolution. A high variability between systems was observed in the measured pressure, with sensor type driving difference between the observed and the predicted pressures. Further research is needed to establish standards and performance analysis of these technologies.